Traumatic Stress Produces Distinct Activations of GABAergic and Glutamatergic Neurons in Amygdala - Fang, Qing; Li, Zhe; Huang, Geng-Di; Zhang, Huan-Huan; Chen, Ya-Yun; Zhang, Li-Bo; Ding, Zeng-Bo; Shi, Jie; Lu, Lin; Yang, Jian-Li (Frontiers in Neuroscience, 2018)
Posttraumatic stress disorder (PTSD), is an anxiety disorder characterized by intrusive recollections of a severe traumatic event and hyperarousal following exposure to the event. Human and animal studies have shown that the change of amygdala activity after traumatic stress may contribute to occurrences of some symptoms or behaviors of the patients or animals with posttraumatic stress disorders (PTSD). However, it is still unknown how the neuronal activation of different sub-regions in amygdala changes during the development of PTSD. In the present study, we used single prolonged stress (SPS) procedure to obtain the animal model of PTSD, and found that 1day after SPS, there were normal anxiety behavior and extinction of fear memory in rats which were accompanied by a reduced proportion of activated glutamatergic neurons and increased proportion of activated GABAergic neurons in basolateral amygdala (BLA). Ten days after SPS, we observed enhanced anxiety and impaired extinction of fear memory with increased activated both glutamatergic and GABAergic neurons in BLA and increased activated GABAergic neurons in central amygdala (CeA). These results indicate that during early and late phase after traumatic stress, distinct patterns of activation of glutamatergic neurons and GABAergic neurons are displayed in amygdala, which may be implicated in the development of PTSD.